Role of Immunohistochemistry in the Differential Diagnosis of Pediatric Renal Tumors: Expression of Cyclin D1, Beta-Catenin , PDGFR-Alpha, and PTEN - Nuray KEPIL; Şebnem BATUR; Zeynep Ecem KAIN; Gamze ÖZCAN; Şenol EMRE; Rahşan ÖZCAN; Tülin Tiraje CELKAN; Nil ÇOMUNOĞLU (Federation of Turkish Pathology Societies, 2022)
Objective: Pediatric renal tumors overlap histomorphologically and may cause misdiagnosis. We aimed to determine the role of immunohistochemical staining of Cyclin D1, PTEN, beta-catenin and PDGFR-alpha on pediatric renal tumors. Material and Method: Thirty-six cases of 8 different tumors were included in the study. Four blocks of paraffin tissue microarray were constructed. Cyclin D1, PTEN, beta-catenin and PDGFR-alpha were used in all cases. Staining intensity and extent were graded. Results: All cases of clear cell sarcoma (CCS) and epithelial components of Wilms tumor (WT) showed immunopositivity for Cyclin D1 but blastemal and stromal components of WT were negative. All cases of CCS and most cases of WT consisting of blastemal and stromal components demonstrated loss of expression with PTEN. Conclusion: Cyclin D1 is not a specific immunohistochemical marker due to its strong and diffuse positivity in CCS cases. It may be useful to differentiate CCS from blastemal and stromal components of WT. Other markers except cyclin D1 do not have a role in the differential diagnosis.